2022
DOI: 10.55275/jposna-2022-0047
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Rate of Operative Management of Proximal Humerus Fractures in Adolescents: A National Database Study

Abstract: Background: There is no consensus on the operative treatment of adolescent proximal humerus fractures. The purpose of this study was to investigate the trends in treatment of proximal humerus fractures in adolescents and identify predictors of operative management. Methods: The Pediatric Health Information System database was used to identify patients ages 10 to 18 diagnosed with proximal humerus fractures between 2004 to 2019. Open fractures were excluded from the analysis. Descriptive, univariate, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…3 Studies have shown proximal humerus fractures to be up 3-4 times more common in males compared with females, though these numbers vary across studies. 2,[4][5][6] Proximal humerus fractures in children below the age of 2 years may occur during the birthing process or as a result of child abuse. [7][8][9][10] Proximal humerus fractures most commonly result from a backwards fall onto an outstretched hand with an extended, abducted, and externally rotated arm.…”
Section: Epidemiology and Mechanism Of Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…3 Studies have shown proximal humerus fractures to be up 3-4 times more common in males compared with females, though these numbers vary across studies. 2,[4][5][6] Proximal humerus fractures in children below the age of 2 years may occur during the birthing process or as a result of child abuse. [7][8][9][10] Proximal humerus fractures most commonly result from a backwards fall onto an outstretched hand with an extended, abducted, and externally rotated arm.…”
Section: Epidemiology and Mechanism Of Injurymentioning
confidence: 99%
“…Overall, there has been a decreasing rate of operative management of adolescent proximal humerus fractures in recent years with considerable geographic variation. 6 There is also difference in management depending on the treating hospital with higher rate of operative management in general hospitals compared to children's hospitals which demonstrates this lack of consensus. 5,6 Management of Fractures with Acceptable Alignment Nonoperative management consists of simple immobilization with a sling or a hanging arm cast.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors increasing likelihood of operative management are older age, male sex, non-Medicaid payer status, increased injury severity score, and admission to an adult hospital [11•, 15•]. The rate of operative management for pediatric proximal humerus fractures is 43.2% across children's and adult hospitals compared to 11.9% at children's hospitals [15,43]. Neuromuscular disorders or nerve palsies which may unpredictably impact muscular forces may also be indications for operative fixation [10].…”
Section: Managementmentioning
confidence: 99%
“…In den letzten Jahren ist trotz zahlreicher Studien, die die große Erfolgsrate der konservativen Therapie zeigten, ein Anstieg der operativen Versorgung zu verzeichnen [ 8 ]. Interessant hierbei ist, dass an Krankenhäusern, die sowohl Erwachsene als auch Kinder- und Jugendliche versorgen, die Rate an operativ versorgten Fällen bei 48,2 % lag, während sie an Kinderkrankenhäusern 11,8 % betrug [ 11 , 13 ]. Akzeptable Toleranzgrenzen unterscheiden sich in der Literatur erheblich.…”
Section: Introductionunclassified